Fluid–particle flow simulations using two-way-coupled mesoscale SPH–DEM and validation - Robinson, Martin; Ramaioli, Marco; Luding, Stefan (International journal of multiphase flow, 2014)
[Display omitted] •We present a simulation method for fluid–particle flows using coupled SPH and DEM.•Purely particle-based method, no prescribed mesh.•Suitable for problems such as free surface flow, complex and/or moving geometries.•Successfully reproduces expected behaviour in 3D sedimentation test cases.•Limitations for too fine fluid resolutions or high porosity gradients are discussed. First, a meshless simulation method is presented for multiphase fluid–particle flows with a two-way coupled Smoothed Particle Hydrodynamics (SPH) for the fluid and the Discrete Element Method (DEM) for the solid phase. The unresolved fluid model, based on the locally averaged Navier Stokes equations, is expected to be considerably faster than fully resolved models. Furthermore, in contrast to similar mesh-based Discrete Particle Models (DPMs), our purely particle-based method enjoys the flexibility that comes from the lack of a prescribed mesh. It is suitable for problems such as free surface flow or flow around complex, moving and/or intermeshed geometries and is applicable to both dilute and dense particle flows. Second, a comprehensive validation procedure for fluid–particle simulations is presented and applied here to the SPH–DEM method, using simulations of single and multiple particle sedimentation in a 3D fluid column and comparison with analytical models. Millimetre-sized particles are used along with three different test fluids: air, water and a water–glycerol solution. The velocity evolution for a single particle compares well (less than 1% error) with the analytical solution as long as the fluid resolution is coarser than two times the particle diameter. Two more complex multiple particle sedimentation problems (sedimentation of a homogeneous porous block and an inhomogeneous Rayleigh Taylor Instability) are also reproduced well for porosities 0.6⩽∊⩽1.0, although care should be taken in the presence of high porosity gradients. Overall the SPH–DEM method successfully reproduces quantitatively the expected behaviour in these test cases, and promises to be a flexible and accurate tool for other, realistic fluid–particle system simulations (for which other problem-relevant test cases have to be added for validation).